Analisis Perbandingan Stimulus Pemasaran dalam Keputusan Pembelian Smartphone Blackberry dan Samsung di Pekanbaru - Alfarisi, Salman; Sulistyowati, Lilis; ', Jushermi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the differences in the stimulus marketingincludes product, price, promotion, distribution channels and service in the purchase decision smartphone Blackberry and Samsung in the city of Pekanbaru. This study was carried out in the city of Pekanbaru. Population in this study is the consumer smartphone in Pekanbaru.This research is use non-probability sampling method. The population is quite large and can not be known with certainty the actual amount, then to determination of the number of samples by using the method of Hair, wich is the number of samples is the number of indicator variables (questions). There were 15 questions, so the number of samples is 5 x 15 = 75 respondents. While the data analysis using the paired t-test (t-test). The results showed that there are differences in marketing stimulus of Samsung and Blackberry Smartphone. The differences between the two smartphone product are quality and price. It can be seen from the value of t-count > t-table and the Sig <0.05. Thus the hypothesis (Ha) research is acceptable. The results also showed that there are differences in consumer decision of Samsung and Blackberry smartphone. The difference lies in the quality of products which include, brand and model as well as the amount of the purchase. It can be seen from the value of t count> t-table and the Sig <0.05. Thus the research hypothesis can be accepted.Keywords: Stimulus Marketing, Purchasing Decisions, Smartphone